QTL‐allele system of main stem node number in recombinant inbred lines of soybean (Glycine max) using association versus linkage mapping. (9th August 2021) - Fahim, Abbas Muhammad; Pan, Liyuan; Li, Chunyan; He, Jianbo; Xing, Guangnan; Wang, Wubin; Zhang, Fengkai; Li, Ning; Gai, Junyi
Abstract: Main stem node number (MSN) as a major plant architectural trait determines the plant canopy and seed yield potential in soybean. To identify the MSN QTL system, a recombinant inbred line (RIL) population consists of 427 lines derived from the cross of KF‐1 × NN1138–2 was tested at two locations in 2 years showing MSN ranging in 11.9–23.7, from which the MSN QTL system was explored using RTM‐GWAS (restricted two‐stage multi‐locus genome‐wide association study) compared with linkage mapping CIM (composite interval mapping). By RTM‐GWAS, 89 QTLs were detected with a phenotypic contribution of 84.50%, whereas by CIM, 24 QTLs detected, indicating the RTM‐GWAS more powerful than CIM. In the population, the best RIL genotypic value was ~24.5, whereas the predicted extreme potential was as high as 49.0. Of the 89 MSN QTLs, 31 ones overlap with those reported in literature, whereas the rest 58 ones are novel. From the QTLs, 74 candidate genes were annotated and GO‐grouped into six categories of biological processes. RTM‐GWAS is potential in exploration of MSN QTL/Gene system benefiting breeding for ideal canopy.